Mismatch Based Diagnosis of PV Fields Relying on Monitored String Currents - Pierluigi Guerriero; Luigi Piegari; Renato Rizzo; Santolo Daliento (International Journal of Photoenergy)
This paper presents a DC side oriented diagnostic method for photovoltaic fields which operates on string currents previously supplied by an appropriate monitoring system. The relevance of the work relies on the definition of an effective and reliable day-by-day target for the power that every string of the field should have produced. The procedure is carried out by comparing the instantaneous power produced by all solar strings having the same orientation and by attributing, as producible power for all of them, the maximum value. As figure of merit, the difference between the maximum allowed energy production (evaluated as the integral of the power during a defined time interval) and the energy actually produced by the strings is defined. Such a definition accounts for both weather and irradiance conditions, without needing additional sensors. The reliability of the approach was experimentally verified by analyzing the performance of two medium size solar fields that were monitored over a period of four years. Results allowed quantifying energy losses attributable to underperforming solar strings and precisely locating their position in the field.